The picture frame: an aesthetic study - Simmel, Georg; Павлова, Олена Юріївна (Київський національний університет імені Тараса Шевченка, 2024)
The translation is supported by the Gerda Henkel Foundation from the publication: Simmel, G. (1902). Der Bildrahmen - Ein ästhetischer Versuch. Der Tag. Nr. 541, 18. November 1902 (Berlin).

Переклад підтримано Фондом Герди Хенкель з публікації: Simmel, G. (1902). Der Bildrahmen - Ein ästhetischer Versuch. Der Tag. Nr. 541, 18 листопада 1902 (Берлін).
Рама картини: естетичне дослідження
Keywords: Георг Зіммель